Top-Up Students Second Language Talk Time through Vlogs - Beena Anil (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2016)
In this technological era, students need a change in everything especially in learning a subject which is considered to be a difficult one for second language learners (SLL). The advent of internet at all levels of learning in the educational arena is a boon to English teachers to improve the communicative skills of students. This paper shows how Vlog (a fusion of video and blog) to be used in an English teaching classroom to improve students’ oral communication. Vlog helps students to practice English even outside the classroom, give instant teacher’s feedback about their performance and can watch fellow students’ performance. This paper discusses how teachers and students can very easily use vlog by understanding the computer mechanism. Keywords: teaching English, communicative skills, Vlog, teacher- student collaboration